2021
DOI: 10.1111/iej.13630
|View full text |Cite
|
Sign up to set email alerts
|

A laboratory study to assess the physical, mechanical, and 3‐D structural properties of nano‐apatite grafted glass fibre‐based endodontic posts

Abstract: Aim To fabricate and characterize nano‐hydroxyapatite (nHA) grafted and non‐grafted glass fibre‐based endodontic posts. Methodology Experimental glass fibre posts were fabricated using silanized nHA grafted (ex‐HA) and non‐grafted glass fibre (ex‐P) reinforced resins. The structural analysis and morphological patterns were analysed with Fourier transform infrared spectroscopy and scanning electron microscopy, respectively. EverStick® glass fibre posts (eS) were used as a control group. The degree of conversion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…The elution of dental resin composites can be increased by incomplete polymerization, in other words the degree of conversion. It is reported that polymerization of dimethacrylate resins is generally incomplete [16], which is why the degree of conversion remains within the range 55-75% for bulk-fill resins. However, although for adequate clinical performance, a conversion rate has not yet been stated, a minimum of 55% is recommended, at least for occlusal restorative layers [7].…”
Section: Discussionmentioning
confidence: 99%
“…The elution of dental resin composites can be increased by incomplete polymerization, in other words the degree of conversion. It is reported that polymerization of dimethacrylate resins is generally incomplete [16], which is why the degree of conversion remains within the range 55-75% for bulk-fill resins. However, although for adequate clinical performance, a conversion rate has not yet been stated, a minimum of 55% is recommended, at least for occlusal restorative layers [7].…”
Section: Discussionmentioning
confidence: 99%
“…Later, the filtrate was dried at 60 °C for 72 h. Then, the samples of both batches were stored in a desiccator to avoid moisture contamination. The structural and morphological patterns of silanized fibers were analyzed by Fourier transform infrared spectroscopy (FTIR; Thermo Fisher Scientific, Waltham, MA, USA) and scanning electron microscopy (SEM; Tescan Vega 3, Brno-Kohoutovice, Czech Republic), as described (images provided in Supplementary Materials , Figure S1 ) in detail previously [ 28 ].…”
Section: Methodsmentioning
confidence: 99%